2009
DOI: 10.1097/sla.0b013e3181952888
|View full text |Cite
|
Sign up to set email alerts
|

Diverticulitis in the United States: 1998–2005

Abstract: We are the first to report dramatic changes in rates of treatment for diverticulitis in the United States. The causes of this emerging disease pattern are unknown, but certainly deserve further investigation. For patients undergoing surgery for acute diverticulitis, there was little change over time in the likelihood of a primary anastomosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
159
3
10

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 518 publications
(179 citation statements)
references
References 17 publications
7
159
3
10
Order By: Relevance
“…14,15 Patients with diffuse peritonitis, resulting from colon perforation, and those for whom conservative management is unsuccessful may require an emergency or elective colectomy.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Patients with diffuse peritonitis, resulting from colon perforation, and those for whom conservative management is unsuccessful may require an emergency or elective colectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Genelikle belirsiz klinik yakınmalara neden olur. Asya toplumlarında divertiküler hastalık sağ kolonda sık görülmesine rağmen, batı toplumlarında genellikle sol kolon yerleşimli olduğu saptanmıştır (3) . Acil yatış gerektiren kolorektal hastalıkların %41'i divertiküler hastalıktır ve bunların yaklaşık olarak %20'si ameliyat edilmektedir (4) .…”
Section: Introductionunclassified
“…These studies have reported a reduction in mortality following hospital admission over time with a reduction from 1.6% in 1998 to 1.0% in 2004-2005 and a 55% relative reduction in in-hospital mortality from 4.5% to 2.5% from [2002][2003][2004][2005][2006][2007] with a reduction in mortality following surgery for acute diverticulitis from 5.7% to 4.3% across the same period. [37] Need for colonoscopy at follow up Current guidelines still recommend routine follow-up colonoscopy after a first attack of acute diverticulitis to confirm the diagnosis and exclude malignancy. [38] The recommendation for colonoscopy after an episode of acute diverticulitis is merely based on expert opinion and dates back to the time before widespread use of CT to diagnose acute diverticulitis.…”
Section: Mortalitymentioning
confidence: 99%